International Archives and National Music Competitions: The Preservation of an “Endangered” Musical Heritage in the Saharawi Refugee Camps (Southwest Algeria) - Violeta Ruano Posada (Transposition, 2019)
The preservation of cultural practices within the framework of the UNESCO ICH lists has been tied to the protection of cultural diversity, intercultural dialogue and community identity. Moreover, it is inextricably linked to questions of national identity, especially given that submissions are made on an (internationally recognised) nation-state basis. This becomes problematic in the case of long-standing unrecognised states, such as the Saharawi Arab Democratic Republic (SADR). The protracted refugee status of the Saharawi people—based in refugee camps in the south-western Algerian desert since Morocco occupied their homeland Western Sahara in 1975—is a major obstacle in their struggle for independence. Their recent history of war, occupation, exile and cultural appropriation has threatened the survival of Saharawi musical and poetic practices, as well as restricting their access to international bodies that could provide cultural safeguarding assistance.To address this situation, the Saharawi cultural authorities have collaborated with international organisations (e.g. the Autonomous University of Madrid and the British Library) to create archives of Saharawi poetry and music. In addition, every year they organise large festivals to showcase traditional culture, featuring musical competitions especially aimed at youth. To prepare for these competitions, young people—who have gradually become less aware of the Saharawi Bedouin way of life before exile—are assisted by national musicians and encouraged to research their own traditional music by establishing dialogues with the elders. So far, these measures have had significant short-term impact on the local population, engaging the youth in anecdotal research on their traditional culture; however, due to the Saharawi government’s chronic lack of resources, it has been impossible both to sustain such measures in the long term and to achieve international recognition.Focusing on two case studies—1) the British Library preservation project “Portraits of Saharawi Music” and 2) a music competition during the Saharawi national celebrations in February 2014—this article explores the efforts of the SADR to safeguard their musical heritage using a mix of material (recorded archives) and non-material (oral transmission) strategies. It also analyses the ways in which socio-political interests such as the reinforcement of a self-built national identity have encouraged the need to keep particular styles (e.g. traditional/national music) alive under the label of intangible heritage preservation.